Vägprojektering - E45 Gällivare - Lundgren, Johan; Simu, Markus (2015)
In this project we have studied the conditions to resolve a problematic traffic situation where traffic is passed through the locality of Gällivare. The traffic that runs through the city in the current situation leads to poorer living quality for the local residents.To solve the identified problems, we chose to create suggestion drawings for a new stretch of a road outside the urban area, using a computer aided design tool. The suggested section is 5.9 km long with a speed limit of 90 km / h.Modelling of the road geometry has been performed in accordance to the Swedish transport administration's requirements for the design of road constructions. As the results shows, we have created drawings in plan, profile and section that follows all modelling requirements.The report also presents a cost estimate for the production of the road. The cost is calculated to 70 million Swedish crowns using a previous reference projects that the Swedish transport administration made in 2012.Uncertainties in the work are presented in a separate chapter, where all uncertainties such as the lack of geotechnical investigations, inaccurate data, traffic etc. are described. Validerat; 20150612 (global_studentproject_submitter)